Sistema de aquisição de dados utilizando microcontrolador Arduino para a tecnologia de aplicação de agroquímicos - Machado, Rafael Vagner de Oliveira (2016)
The use of plant protection products is very important for most agricultural production systems, but it is clear that these products pose risks to the environment and human health. The application of technology should be planned and monitored in a responsible manner, in order to seek its improvement and to minimize the potential damage to the environment. Observing these facts, this study aims to develop a data acquisition system (DPS) low cost for obtaining and storage technology application-related data, as working pressure, Rotation Power Outlet, temperature and relative humidity, travel speed, besides obtaining the geographic coordinates and determine the area worked by the machine by means of GPS. The equipment is based on an Arduino Mega 2560 R3 board, which coordinates the sensors used and performs the manipulation of data, Furthermore SAD has a man-machine consists of an LCD display interface and pushbotton type of pressure switches and a memory card module to store the collected data. With SAD prototype ready tests were carried out with the sensors and the GPS module in the field. For the static test was conducted on GPS geodetic station located at 92426 IFRN Mossoró / RN, it was observed that the average of the coordinates obtained by the GPS module used has reached a distance of 0.6 m with respect to geodetic station. With the end of the work can be concluded that the SAD is developed a robust equipment, easy to handle and affordable for small and medium producers. The system features an intuitive man-machine interface, providing easy and quick access to all configuration parameters and features of the equipment